Design of Prototype of Solar Power Based Waste Water Treatment Plant - Djusdil Akrim; Ahmad Swandi; Muhammad Fikruddin Buraerah; Andi Irwandi; Syahrul Sariman; Hamsina (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to find out an overview of the prototype solar power-based Waste Water Treatment Plant (WWTP), the component requirements of the PLTS system as an energy source for the WWTP, and level of efficiency in using solar power plants in IPAL operations. The type of research used is experimental research. Based on the research results a prototype solar power-based IPAL system has been produced with a capacity of 800 liters per hour or 11,200 liters per day (14 operational hours) with a Biotech/biofilter type modified by adding a water filter after the chloronization process. Besides of that, a source of electrical energy for all electrical components of the WWTP with a solar panel and battery capacity of 200 wattpeak and 100 Ah respectively. The efficiency level of the solar panels used reached 88.36% at 12.00 (very sunny weather conditions) with input power above output power in the range 09.00-16.00. With this efficiency, electrical energy can be stored to operate the WWTP at night.